2023
DOI: 10.1108/jarhe-05-2023-0195
|View full text |Cite
|
Sign up to set email alerts
|

Exploring key themes and trends in international student mobility research —A systematic literature review

Abstract: PurposeThe global landscape of higher education has witnessed a steady increase in the mobility of international students, as more individuals seek diverse academic experiences and cross-cultural learning opportunities. This paper conducts a systematic literature review to investigate trends, research directions and key themes in the literature. By utilising the push–pull factor model the aim is to provide a comprehensive understanding of the factors influencing international students' choices to pursue higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Educational researchers have employed the push-pull model to explain international students' mobility, their decisions to study abroad, the selection of the destination country and educational institution (Chen, 2007;Gbollie and Gong, 2019;Gesing and Glass, 2019;Gutema et al, 2023;Li and Bray, 2007;Mazzarol and Soutar, 2002;Nikou and Luukkonen, 2023). Agarwal and Winkler (1985) found that the cost of education, home country opportunities, perceived benefits and per capita income can impact students from developing countries who wish to study in the USA.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Educational researchers have employed the push-pull model to explain international students' mobility, their decisions to study abroad, the selection of the destination country and educational institution (Chen, 2007;Gbollie and Gong, 2019;Gesing and Glass, 2019;Gutema et al, 2023;Li and Bray, 2007;Mazzarol and Soutar, 2002;Nikou and Luukkonen, 2023). Agarwal and Winkler (1985) found that the cost of education, home country opportunities, perceived benefits and per capita income can impact students from developing countries who wish to study in the USA.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%